Educação profissional no cárcere feminino: uma proposta emancipatória - Cruz, Elizete Helena Alves da (2018)
The interest in the subject "professional education in the prison" began after insertion in the group of studies and research on "Education and Gender" and project of extension." From captivity to freedom: narratives of stories of women prisoners"; followed in the Specialization course of the Post-Graduate Program in Educational Management (CE/UFSM). In this formative itinerary, my attention was focused mainly on the anxieties of women distressed about the need for schooling and / or professional qualification in the prison environment, which was decisive for the deepening of the issue at the Master level: "Professional education in the female prison: an emancipatory proposal". In this qualitative study, the research methodology used was the bibliographical review and semistructured interviews with the representatives of educational, jurisdictional, labor, distressed and egressed institutions. In view of the need for a shared reflection movement and together with other knowledge and formative experiences about professional education in the environments of deprivation of freedom - and to what extent this educational modality can help in the emancipatory process - is that the present study finds its justification The research aimed to analyze professional education in prison as an educational process that aims at the emancipation of the human being, being indispensable the Freire's reading (1996) from the practice, since to know is to fight to access a transformative knowledge and assume a vigilant stance against all dehumanizing practices. In fact, Butler (2010) appears to be the category of women produced and repressed by the same structures of power by means of which emancipation is sought. However, Louro (1997) infers that relations of inequality are built and reproduced in the social field, and it is necessary to reinsert the issue in all areas of debate. In fact, understanding the educational system and the school practices in the administrative, technical, political, legal, pedagogical, methodological and gender aspects makes possible the collective construction of the political-pedagogical project in prison spaces and times before the challenges to the educational process and difficulties faced by the schools inserted in these environments. Therefore, it is believed that professional education is an essential proposition for women deprived of their liberty so that they can (re)enter into the world of work, employment and income and be protagonists of their own history.